Advances in the endovascular treatment of direct carotid-cavernous fistulas - Aguiar,Guilherme Brasileiro de (2016)
SUMMARY Carotid cavernous fistulas (CCFs) are abnormal connections between the carotid artery and the cavernous sinus. They are considered direct when there is a direct connection between the internal carotid artery and the cavernous sinus. These cases are generally traumatic. Direct CCFs are high-flow lesions, possibly related to intracranial bleeding, visual loss, corneal exposure or even fatal epistaxis. Treatment of such lesions is, thus, always recommended. The ideal treatment for direct CCF is to exclude the fistula from circulation, preserving the carotid flow. This can be attained using diverse endovascular techniques. The objective of the present article is to review the current techniques for treatment of direct CCFs, with special attention to the currently available endovascular treatment options.